Erosion of sand screens: A review of erosion prediction modelling approaches - Abduljabbar, A. (Elsevier B.V., 2022)
Sand production in unconsolidated oil and gas reservoirs is a major challenge. The entrained sand can cause erosion of the production components. Sand screens are widely used to eliminate or minimise sand production. However, the screen itself may become ineffective when eroded. Therefore, predicting screen erosion is an essential part of proper design. However, owing to the complexity of the erosion phenomena, obtaining a universal model for all flow conditions is challenging. Nevertheless, several prediction models are available in the literature. In this study, published models are presented, discussed, and analysed. A summary of the empirical erosion models is presented to identify the potential areas to be developed. In addition, the limitations of some of these models have been highlighted. In addition, challenging considerations and future studies regarding CFD-based modelling are discussed. The study revealed that the empirical models require improvements to account for high sand concentrations and multi-angle collisions. Â© 2022 Elsevier B.V.